TINJAUAN EARNING RATIO PADA BANK PERKREDITAN RAKYAT (BPR) YANG ADA DIKOTA PADANG - Endang Afriyeni; Jumyetti Jumyetti (Politeknik Negeri Padang, 2018)
The study aims to find out and measure the Earning Ratio of Rural Banks that were in the city of Padang during 2014-2016. ROA as one of the indicators used to measure earnings from a bank. Data was obtained from six Rural Banks in the city of Padang. The result were that during 2014 until 2016 the highest ROA ratio was 2.75% while the lowest was -3.73% (in 2016). The ROA ratio of the six Rural Banks in the city of Padang shows that only the Third Rural Bank shows the Healthy criteria for two consecutive years (2016, 2015). Whereas the First Rural Bank was only in 2016 included in the criteria of Healthy. The criteria for Healthy Enough is only one year successfully achieved by the Second Rural Bank, Fifth Rural Bank and Sixth Rural Bank. Whereas the Fourth Rural Bank for three consecutive years is unhealthy. This means that the Rural Bank has not been efficient in managing its assets to generate profits during 2014-2016.